2020
DOI: 10.1016/j.agee.2019.106797
|View full text |Cite
|
Sign up to set email alerts
|

Landscape heterogeneity of peasant-managed agricultural matrices

Abstract: In agricultural landscapes, management practices and other environmental and social factors shape complex agroecological matrices. In turn, the structure of such matrices impacts both agricultural activities and biodiversity conservation, for instance, by mediating wildlife migration between agricultural and habitat patches. One way to characterize a matrix, its potential role in biodiversity conservation, and how its descriptors change across different spatial scales, is characterizing heterogeneity metrics a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…In particular, curculionids maintained a good correlation with overall coleopteran biodiversity, as well as with management intensification. In another work in Zaachila (Urrutia et al 2019), we showed that agricultural patches, specially rainfed-agriculture patches, dominate this rural landscape and that, given their atomized pattern and large connectivity, they play a central role in the potential migration and recolonization among the adjacent forest patches. Together, these two studies suggest that traditional agriculture being practiced in the agricultural patches of Zaachila would render a high quality matrix for biodiversity conservation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In particular, curculionids maintained a good correlation with overall coleopteran biodiversity, as well as with management intensification. In another work in Zaachila (Urrutia et al 2019), we showed that agricultural patches, specially rainfed-agriculture patches, dominate this rural landscape and that, given their atomized pattern and large connectivity, they play a central role in the potential migration and recolonization among the adjacent forest patches. Together, these two studies suggest that traditional agriculture being practiced in the agricultural patches of Zaachila would render a high quality matrix for biodiversity conservation.…”
Section: Discussionmentioning
confidence: 87%
“…It is a semi-urban population located 17 km southeast of the state's capital. The most represented land use types are agriculture, which covers 48 % of its total area, secondary forest with 23 % and urban zones with 19 % (Urrutia at al. 2019).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…(2) LAI refers to the ability of the landscape to adapt and self-recover under external disturbances, which consists of plaque rich density index (PRD) [24], Shannon diversity index (SHDI) [25], and Shannon uniformity index (SHEI) [25]. Combined with the detailed introduction of the three indices in the references, the specific calculation process can be completed in ArcGIS10.5.…”
Section: Landscape Vulnerability Index (Lvi)mentioning
confidence: 99%
“…In this work, we sampled the beetle community in plots belonging to a highly heterogeneous, peasant-driven agricultural landscape (Urrutia et al, 2020). We worked in the Central Valleys of Oaxaca, Mexico, a region recognized for its extraordinary biological and cultural diversity, and that is in many ways representative of small-scale agriculture landscapes in southern Mexico (Mora Van Cauwelaert, 2017;Ramos, 2020;Urrutia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%